PENGARUH BEBAN KERJA TERHADAP KEPUASAN KERJA DENGAN STRES KERJA SEBAGAI VARIABEL MEDIASI PADA PEKERJA DI HOTEL MAXONE DI KOTA MALANG - Andri Wijaya (Ma Chung Press, 2018)
Job satisfaction is one of several factors that are very important to get the desired work. This study aims to examine the effect of workload on job satisfaction with job stress as a mediation variable. The study was conducted at Maxone Hotel Malang by distributing questionnaires directly to all its 80 workers. Path analysis shows that work stress mediated the effect of workload on job satisfaction. In other words, the effect of workload on job satisfaction is not directly. Work load positively affects work stress; job stress has a negative effect on job satisfaction. That is, the higher the workload, the higher the level of work stress, and this may cause decreasing job satisfaction.